Menelaus' ›Spherics‹ : Early Translation and al-Māhānī / al-Harawī's Version - Rāshid, Rushdī; Papadopoulos, Athanase (Scientia Graeco-Arabica, 2017)
Despite its importance in the history of Ancient science, Menelaus' Spherics is still by and large unknown. This treatise, which lies at the foundation of spherical geometry, is lost in Greek but has been preserved in its Arabic versions. The reader.